Hydraulic Transients Induced by Pigging Operation in Pipeline with a Long Slope - Tao Deng; Jing Gong; Haihao Wu; Yu Zhang; Siqi Zhang; Qi Lin; Huishu Liu (Journal of Applied Mathematics)
Pigging in pipelines basically performs operations for five reasons including cleaning the pipe interior, batching or separating dissimilar products, displacement, measurement, and internal inspection. A model has been proposed for the dynamic simulation of the pigging process after water pressure testing in a long slope pipeline. In this study, an attempt has been made to analyze two serious accidents during pigging operation in 2010 by the model which is developed by the method of characteristic (MOC) by Wylie et al. (1993) and the two-phase homogeneous equilibrium vaporous cavitation model deveoped by Shu (2003) for vaporous cavitation. Moreover, simulation results of the third operation show good agreement with field data from the previous field trial. After investigation, it was showed that the impulse pressures produced during collapse of a vapor cavity result in severe damage of tubes.